(untitled) (Texas Journal of Philology, Culture and History, 2023)
In this article, Persian-Tajik plant names used in Alisher Navoi’s epic "Saddi Iskandari", their semantic analysis, phonetic features of Persian plant names in the epic, fruit names, vegetable names, flower names, ornamental plant names, Alternatives of fruit names, plant names are included in the list of lexical units that actively participate in the formation of displacements, expressiveness and emotionality characteristic of the artistic text, comments on plant names by linguists are discussed.